2022
DOI: 10.1073/pnas.2110196119
|View full text |Cite
|
Sign up to set email alerts
|

LRRTM3 regulates activity-dependent synchronization of synapse properties in topographically connected hippocampal neural circuits

Abstract: Synaptic cell-adhesion molecules (CAMs) organize the architecture and properties of neural circuits. However, whether synaptic CAMs are involved in activity-dependent remodeling of specific neural circuits is incompletely understood. Leucine-rich repeat transmembrane protein 3 (LRRTM3) is required for the excitatory synapse development of hippocampal dentate gyrus (DG) granule neurons. Here, we report that Lrrtm3-deficient mice exhibit selective reductions in excitatory synapse density and synaptic strength in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…[87][88][89] Extensive anatomical analyses using LRRTM3 cKO mice demonstrated that LRRTM3 is required for maintaining excitatory synaptic inputs in both DG granule neurons and hippocampal CA3 pyramidal neurons. [88] In addition, LRRTM3 was shown to be required for maintaining normal synapse morphologies (i.e., MF boutons and thorny excrescences), as assessed by high-resolution three-dimensional scanning electron microscopy. [88] Electrophysiological recordings revealed that LRRTM3 is required to maintain LTP in the perforant and MF pathways.…”
Section: Lrrtm3 Controls the Excitatory Synapse Number And Synaptic S...mentioning
confidence: 99%
See 4 more Smart Citations
“…[87][88][89] Extensive anatomical analyses using LRRTM3 cKO mice demonstrated that LRRTM3 is required for maintaining excitatory synaptic inputs in both DG granule neurons and hippocampal CA3 pyramidal neurons. [88] In addition, LRRTM3 was shown to be required for maintaining normal synapse morphologies (i.e., MF boutons and thorny excrescences), as assessed by high-resolution three-dimensional scanning electron microscopy. [88] Electrophysiological recordings revealed that LRRTM3 is required to maintain LTP in the perforant and MF pathways.…”
Section: Lrrtm3 Controls the Excitatory Synapse Number And Synaptic S...mentioning
confidence: 99%
“…APP acts as a presynaptic CAM to trans-synaptically regulate GABAergic synaptic strength and synapse number, and these parameters are negatively tuned by the action of postsynaptic MDGA1 in the dendritic, but not somatic, compartment of hippocampal CA1 pyramidal neurons (middle). AMPAR, α-amino-3-hydroxy-5-methyl-4-isoxacolepropionic acid receptor; APP, amyloid precursor protein; CAM, cell adhesion molecule; Cbln, cerebellin precursor; DG, dentate gyrus; GABA A R, γ-aminobutyric acid type A receptor; GluD, glutamate receptor δ family; IgSF, immunoglobulin superfamily; LEC, lateral entorhinal cortex; LRRTM, leucine-rich repeat transmembrane protein; Lphn, latrophilin; MDGA1, MAM domain-containing glycosylphosphatidylinositol anchor protein 1; MEC, medial entorhinal cortex; NMDAR, N-methyl-D-aspartate receptor; Nrxn, neurexin; PV, parvalbumin; PTPσ, protein tyrosine phosphatase sigma; SLM, stratum lacunosum-moleculare; SP, stratum pyramidale; SO, stratum oriens; SR, stratum radiatum; SST, somatostatin; Sub, subiculum in the medial, but not lateral, perforant pathway, [88] indicating that LRRTM3 is critical in conferring neural circuit specificity. LRRTM3 cKO neurons exhibit enhanced neurotransmitter release, which might regulate the excitability of DG granule neurons and MF-LTP, [88] suggesting that medial perforant and MF pathways activities are inter-dependent.…”
Section: Lrrtm3 Controls the Excitatory Synapse Number And Synaptic S...mentioning
confidence: 99%
See 3 more Smart Citations